Indulgences for Prayers for the Dead in the Diocese of Lincoln in the Early Fourteenth Century - Swanson, R. N. (The journal of ecclesiastical history, 2001)
The role of indulgences in pre-Reformation English religion remains incompletely studied. Centred on material contained in the Lincoln episcopal registers dating from c. 1290 to c. 1340, granting indulgences for prayers for the souls of named people and often specifying their burial locations, this article argues that their place in medieval spirituality and charitable activity has been under- appreciated. Examining the mechanisms and implications of the Lincoln records, it suggests that under-recording of actions considered normal and routine, rather than lack of popularity, lies behind the failure to give indulgences their due place in assessment of English medieval religious life.